Development of bottom cavity of 4 liter bottle - Wan Ahmad Saiful, Wan Muhamad Sukeri (2007)
Four liter plastic bottle always use in chemical industry. A good of mold will need to produce a high quality of four liter plastic bottle. Actually the mold for this bottle is dividing into three parts. They are top cavity of bottle, main cavity of bottle and bottom cavity of bottle. This project will show how and what are the processes that involve developing the bottom cavity of four liter bottle. These projects start with initially in design stages, material selection for bottom cavity mold and fabricate the mold. The latest technologies that use to fabricate the mold are Master Cam software and CNC milling machine. Another processes are use to ensure no defect and follow the characteristics from actual specification.